Nonstationarity analysis in wind-rain-induced vibration of stay cables - He, Xu-hui; Yu, Xiang-dong; Chen, Zheng-qing (Journal of Civil Engineering and Management, 2012)
Wind and wind-rain-induced cable vibration are usually nonstationary. Based on the field measured wind data from the Dongting Lake Bridge (DLB) in China, a wavelet-based method was developed to investigate the wind characteristics of wind-rain-induced cable vibration. By using the wavelet analysis, the time-varying mean wind speed is extracted and a nonstationary wind speed model is proposed. The turbulence intensities and probability distributions of measured wind data are calculated using the proposed nonstationary model and compared with those based on empirical mode decomposition (EMD) and design values. The correlation between wind and wind-rain-induced acceleration response are discussed. At the same time, the relativity of acceleration responses of cable and the wind speed are discussed via calculating root mean square (RMS) averaging and acceleration response peak factors.